The Role of Institutional Quality in Shaping Digital Governance in Decentralised Indonesia - Wais Alqarni; Safrizal ZA; Isnaini Muallidin; Afrijal Afrijal; M Nur Akhyar (Journal of Contemporary Governance and Public Policy, 2026)
This study examines how institutional quality shapes digital governance across local governments in Indonesia, addressing the persistent institutional–technical misalignment that continues to hinder digital transformation despite substantial public investment. The study is motivated by efforts to localise the United Nations Sustainable Development Goals, particularly SDG 16, Targets 16.6 and 16.7, on effective, accountable, and transparent institutions and responsive, inclusive, participatory, and representative decision-making, as well as SDG 9, Target 9.c, on universal internet access. Achieving these goals remains difficult across Indonesia’s diverse regional contexts because of entrenched institutional barriers. Using a qualitative multiple-case study design, this research analyses five subnational cases, Jakarta, West Java, East Kalimantan, South Sulawesi, and Papua, selected to capture varying levels of digital maturity and contrasting geographical conditions within Indonesia’s decentralised governance system. The findings indicate that four institutional dimensions, regulatory frameworks, organisational capacity, leadership commitment, and inter-agency coordination, decisively shape digital governance outcomes and mediate regional disparities. The study concludes that digital transformation in decentralised systems is fundamentally an institutional rather than purely technological process. It proposes an integrated institutional quality framework to strengthen decentralised digital resilience and improve public service delivery across Indonesia’s fragmented governance landscape.